A Virtual Prototyping System Research and Implementation in a Collaborative PLM Environment. (2016) - Moldovan, Catalin Constantin; Staretu, Ionel
Abstract: This paper introduces a new approach to virtually prototyping by using digital human hands models and hand posture for grasping and controlling objects in virtual worlds. The actual part design is done using existent on the market CAD software. This paper presents also the conceptual architecture of a collaborative PLM environment. More precise, a conceptual PLM system architecture which contains a virtual prototyping framework, functional simulation framework and an information exchange infrastructure is proposed in this paper along with a newly defined protocol for CAD data exchange from one CAD system to another.